2019
DOI: 10.3390/polym11040628
|View full text |Cite
|
Sign up to set email alerts
|

Functional Nanostructured Oligochitosan–Silica/Carboxymethyl Cellulose Hybrid Materials: Synthesis and Investigation of Their Antifungal Abilities

Abstract: Functional hybrid materials were successfully synthesized from low-cost waste products, such as oligochitosan (OCS) obtained from chitosan (one of the main components in crab shells) and nanosilica (nSiO2) obtained from rice husk, in a 1:1 ratio (w/w), and their dispersion in the presence of carboxymethyl cellulose at pH 7 was stable for over one month without aggregation. The molecular weights, chemical structures, morphologies, and crystallinities of the obtained materials were characterized by GPC, FTIR, TE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…SiO 2 nanoparticles were synthesized according to a previously reported procedure. 19,20 Preparation of Lignin from the Rice Husk. RHs were rinsed with water to wash off dirt and other soluble impurities before getting dried at 60 °C.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…SiO 2 nanoparticles were synthesized according to a previously reported procedure. 19,20 Preparation of Lignin from the Rice Husk. RHs were rinsed with water to wash off dirt and other soluble impurities before getting dried at 60 °C.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…Figure 5 shows the XRD patterns of PNS (a) and HMSN (b). As shown, the broad XRD reflection peaks of PNS (2θ = 21.1 • ) and HMSN (2θ = 23.0 • ) both indicate the amorphous nature of silica nanoparticles [31]. In addition, apart from a small amorphous bump at 37 • in the PNS sample that could be attributed to trace CTAB left after calcination, no considerable difference was found between the two XRD patterns of PNS and HMSN, indicating that these nanoparticles likely have similar structures.…”
Section: Resultsmentioning
confidence: 77%
“…Having said that, further investigations on strategies to modify the surface of HMSN are still required to improve the controllability of this system, due to its similar nature to silica nanoparticles, whose availability for functionalization is abundant [4,34]. [31]. In addition, apart from a small amorphous bump at 37° in the PNS sample that could be attributed to trace CTAB left after calcination, no considerable difference was found between the two XRD patterns of PNS and HMSN, indicating that these nanoparticles likely have similar structures.…”
Section: Resultsmentioning
confidence: 99%
“…The same team found that silica and hybrid material had good antifungal properties against P. infestans , the causal organism for late blight in tomato and potato, but the antifungal properties of hybrid materials, due to their synergistic effect, had better antifungal capacities than that of each individual component. Interestingly, the inhibition zone diameters of OCS/nSiO 2 were approximately 4–5 mm and 7–9 mm larger than those of OCS and nSiO 2 , respectively [ 87 ]. Bio-synthetized MgO nanoparticles are produced using the native bacterial strain like Bacillus sp.…”
Section: Nanocomposites and Their Mode Of Action On The Fungal Phymentioning
confidence: 99%